Sensitive Fluorescence Assay for the Detection of Alkaline Phosphatase Based on a Cu2+-Thiamine System - Han Zhao; Xinfa Liu; Changbei Ma (Sensors, 2021)
The authors describe a novel, facile, and sensitive fluorometric strategy based on a Cu2+-thiamine (Cu2+-TH) system for the detection of alkaline phosphatase (ALP) activity and inhibition. The principle of the method is as follows. Under a basic conditions, TH, which does not exhibit a fluorescence signal, is oxidized into fluorescent thiochrome (TC) by Cu2+. Ascorbic acid 2-phosphate (AAP), which is the enzyme substrate, is hydrolyzed to produce ascorbic acid (AA) by ALP. The newly formed AA then reduces Cu2+ to Cu+, which prevents the oxidation of TH by Cu2+; as a result, the fluorescent signal becomes weaker. On the contrary, in the absence of ALP, AAP cannot reduce Cu2+; additions of Cu2+ and TH result in a dramatic increase of the fluorescent signal. The sensing strategy displays brilliant sensitivity with a detection limit of 0.08 U/L, and the detection is linear in the concentration range of 0.1 to 100 U/L. This approach was successfully applied to ALP activity in human serum samples, indicating that it is reliable and may be applied to the clinical diagnosis of ALP-related diseases.